Pengaruh Pemberian Seduhan Daun Mint Pada Ibu Hamil Trimester I Terhadap Penurunan Frekuensi Mual dan Muntah Di Bidan Praktek Mandiri Dewi Martina S.Keb Pujud Kabupaten Rokan Hilir Riau - Hasanah Hsb, Ustifina; Pane, Herviza Wulandary (Jurnal Masyarakat Indonesia (Jumas), 2023)
Common problems that often occur in the first trimester of pregnancy are nausea and vomiting. Even though it is common and does not harm pregnant women, if it is not treated properly it will have an impact on weight loss. Maintaining pregnancy is very important so that the health of the mother and baby is maintained until the birth process. The safest non-pharmacological way to deal with this, one of which is an infusion of mint leaves. This study aims to determine the effect of giving mint leaf infusion to pregnant women in the first trimester on reducing the frequency of nausea and vomiting. This type of research is quantitative with a pre-experimental design on one group of subjects. The total sample was 30 pregnant women in the first trimester using purposive sampling. Research location in Pujud, Rokan Hilir, Riau, Indonesia. Statistical data analysis used the Wilcoxon test. The results of the study showed that administration of mint leaf infusion had a significant effect on reducing the frequency of nausea and vomiting in first trimester pregnant women. This proves that the therapeutic benefits of mint leaves are able to overcome nausea and vomiting. The contribution of this research is evidence of the benefits of mint leaf infusion and as a recommendation as an alternative therapy to reduce nausea and vomiting.